2017
DOI: 10.1080/10503307.2017.1301690
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of metacognitive therapy for hypoactive sexual desire disorder among Iranian couples

Abstract: MCT affected sexual desire more than MJST as evaluated after therapy but the gain was not maintained at follow-up. Future research needs to investigate whether a greater focus on metacognitive beliefs about sexual behavior can improve the stability of treatment effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
6
0
2
Order By: Relevance
“…With few exceptions, the reported comorbidity rates were high. Four studies did not report comorbidity rates, and one study (Ramezani et al, 2017 ) excluded patients with comorbid disorders. For the 17 studies that reported comorbidity rates in percentages, the mean for the MCT conditions was 65% (standard deviation 24, range 0–100%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With few exceptions, the reported comorbidity rates were high. Four studies did not report comorbidity rates, and one study (Ramezani et al, 2017 ) excluded patients with comorbid disorders. For the 17 studies that reported comorbidity rates in percentages, the mean for the MCT conditions was 65% (standard deviation 24, range 0–100%).…”
Section: Resultsmentioning
confidence: 99%
“…The vast majority of studies ( n = 18) followed a published disorder-specific treatment manual for the primary disorder, whereas four studies followed the generic model of intervention as presented by Wells ( 2009 ). Three studies (Rabiei et al, 2012 ; Morrison et al, 2014 ; Ramezani et al, 2017 ) investigated a psychological disorder for which no formal manual had yet been developed. In these cases, the authors had adapted a treatment manual for another disorder to the disorder in question.…”
Section: Resultsmentioning
confidence: 99%
“…By addressing these underlying cognitive processes, couples can improve communication, emotional regulation, and overall relationship dynamics (20). Research findings have confirmed the effectiveness of metacognitive therapy in improving dysfunctional communication patterns, and self-control in couples (21,22).…”
Section: Introductionmentioning
confidence: 74%
“…There is no MCT model described for sexual disorders. A novel study by Ramezani et al (2017) [ 65 ] studied the impact of MCT (using the depression model of MCT proposed by Wells, 2009 [ 1 ]) in a multi-center, RCT (n = 30) among patients with hypoactive sexual desire disorder. The intervention arm received MCT, and the control arm was administered Masters-Johnson Sex Therapy (MJST).…”
Section: Reviewmentioning
confidence: 99%